Rancang Bangun Sistem Pematangan Buah Pisang Berbasis Internet Of Things (IOT) - Ramli Ahmad; Yuli Laily Niswani; Intan Komala Dewi Patwari (Fakultas Teknik Universitas Hamzanwadi, 2026)
The agricultural sector plays an important role in meeting the national food needs, particularly in the production of fruit. However, the storage and marinating of agricultural products still traditionally uses chemicals which may impair crop quality and pose risks to health and the environment. The development of Internet of Things (IoT) technologies offers more secure, efficient and controlled solutions through automated and real-time monitoring systems. The aim of this research is to design and build an Internet of Things-based banana ripening system capable of improving the safety, efficiency and quality of the ripening process. The research method used shall be an experimental method, testing all components of the system. The system is built on a microcontroller ESP32-CAM, a colour sensor for the detection of ripeness based on colour intensity, a DHT22 sensor for monitoring water temperature and humidity, a vibrating alarm for the environmental conditions and a Telegram application for real-time notifications. The test results showed that the colour sensor could distinguish between the condition of immature and mature fruit, indicating the inactive warning when green and active warning when yellow, and the notification sent to the user. The DHT22 sensor registers the average temperature and humidity between 27.50 and 33.20 degrees Celsius and if it exceeds this value, the cooling system is activated and a warning is sent. If network conditions are slow, there are delays in the delivery of notifications of around ±2-5 seconds. In conclusion, the developed maturity system, which is based on the Internet of Things, is capable of working automatically, securely and efficiently to monitor and control the maturity process in real time, with the potential to improve the quality and the value of agricultural products.